Kur’ân’a Göre Medine Dönemi Cihad Tebliğ İlişkisi - Kurt, İsmail (Sırnak University, 2023)
Bu çalışmada Medine dönemi cihad-tebliğ ilişkisi Kur’ân merkezli olarak ele alınmaktadır. Çalışmamızın amacı Medine dönemindeki Allah yolunda cihad ile İslam’a davet arasındaki ilişkiyi olgu-nas diyalektiği çerçevesinde Medenî sureler ve kısmen de siyer üzerinden kronolojik olarak ortaya koymaktır. Yapılan çalışmalarda siyer merkezli olarak özellikle Medine dönemindeki askeri cihada değinilirken Medine dönemi cihad-tebliğ ilişkisi Kur’ân merkezli olarak ele alınmamıştır. Bu çalışmanın ana iskeletinin Kur’ân üzerinden kurulması ve cihad-tebliğ ilişkisinin eşit şekilde birlikte irdelenmesi bu araştırmayı diğer çalışmalardan ayırmaktadır. Çalışmada nitel araştırma yöntemlerinden biri olan doküman, literatür tarama ve analizi yöntemi kullanılmıştır. Yine çalışmada sure kronoloji konusunda genel olarak Câbirî’nin (1936-2010) Fehmü’l-Kur’ân’da takip ettiği sıralamaya uyulmuş, Medenî surelerdeki ayetler ele alınırken Mukâtil (öl. 150/767), Taberî (öl. 310/923), İbn Hişâm (öl. 218/833), Buhârî (öl. 256/870), Derveze (1888-1984) gibi klasik ve modern dönem müelliflerinin verdiği siret bilgisinden de istifade edilmiştir. Çalışmada ulaştığımız en genel bulgu ve sonuçlar ise şunlardır: Medine’ye hicretle birlikte değişen olgu Medine’de vahyin üslûbunun değişmesine ve cihad-tebliğ yönteminin farklılaşmasına yol açmıştır. Olgu ve nas değişmekle birlikte Allah yolunda cihadın ve İslam’a davetin nasıl yapılacağını ise her zaman Kur’ân belirlemiştir. Mekke’de sabır ve hicret şeklinde yapılan cihad ve tebliğ, olgunun değişmesiyle birlikte Medine’de daha çok infak ve savaş şeklinde yapılmıştır. Yine İslam’a davet bağlamında Medine’de Hz. Peygamber’e hiçbir zaman “sabret” denilmemiş, “sabredin” hitabı Müslümanlara yöneltilmiştir. Genel olarak Medine dönemi cihad-tebliğ ilişkisini Hudeybiye Barışı öncesi ve sonrası şeklinde iki farklı döneme ayırabiliriz. Medine’ye hicretle birlikte İslam davetinin muhatabına Yahudiler, münafıklar, Medine’ye gelen heyetler, Kureyş dışındaki müşrik Araplar dahil olsa da Mekke müşrikleri her zaman cihadın ve tebliğin esas muhatabı olmuştur. Kureyş’in Mekke’de başlayan İslam davetini engelleme girişimi Medine döneminde yapılan üç büyük cihad/savaş ile durdurulmuş, Hudeybiye Anlaşması ile İslam davetinin önü açılmış, Mekke Fethi ile de İslam’ın önündeki en büyük engel tamamen ortadan kaldırılmıştır. Hicretle birlikte Medine’deki eski statülerini kaybeden Medine Yahudilerinin İslam davetine düşmanlık etmesi Müslümanların onlara karşı da cihad etmesine yol açmıştır. Medine döneminde savaş ve seriyyelerin yanı sıra evlilikler yoluyla da İslam davetinin önündeki engeller kaldırılmaya çalışılmıştır. Vahyin apaçık bir fetih dediği Hudeybiye Barışı İslam’ın tebliğinde önemli bir dönüm noktası olmuştur. Hudeybiye Barışı İslam’ın tebliğinin emniyet ve güven içinde yapılmasının, Bizans, Sasani gibi büyük devletlere davet mektuplarının gönderilmesinin yolunu açmış ve özellikle Kureyş’ten korkan Hicazdaki müşrik Arapların İslam’a katılmasını hızlandırmıştır. İslam’a davet yolunda ne Kur’ân ne de Hz. Peygamber için savaş hiçbir zaman ana hedef olmamıştır. Asıl gaye her zaman insanların gönüllerinin İslam’a kazandırılması olmuştur. Bu nedenle Kur’ân, azılı düşman Kureyş barışa yanaşırsa Müslümanların da barışa yanaşmasını salık vermiştir. Aynı şekilde Hz. Peygamber de bir müminin eliyle tek bir insanın Müslüman olmasının, kişinin alacağı en değerli ganimetten daha hayırlı olduğunu vurgulamıştır. Sonuç olarak Mekke’de “Ey Peygamber! kalk ve insanları uyar” şeklindeki ilk vahiylerle başlayan İslam’a davet ve cihad, Medine döneminin sonundaki Veda Haccı’nda Hz. Peygamber’in “Allah’ım! tebliğ ettim mi?” hitabına kadar vahyin belirlemesi doğrultusunda devam etmiştir.

In this study, the relationship of jihad and invitation in the Medina period is discussed based on the Quran. The aim of the study is to chronologically reveal the relationship between jihad in the way of Allah and the invitation to Islam in the Medina period within the framework of the phenomenon-text dialectic based on Medina suras and partly on the information of the sirah. In the studies carried out, especially the military jihad in the Medina period was mentioned as sirah-centered, the jihad-invitation relationship in the Medina period was not discussed based on the Quran. Establishing the main framework of the study through the Quran and examining equally the jihad- invitation relationship distinguish this research from other studies. During the study, document analysis, literature review and analysis method, some of the qualitative research methods, were used. Again, in the study, the order that Jabiri followed in Fahm al-Quran was followed in general in terms of surah chronology. While dealing with the verses in Medinan suras, the knowledge of sirah given by classical and modern authors such as Mukatil, Tabari, Ibn Hisham, Bukhari and Darwaza has also been utilized. The most general findings and conclusions reached in this study are as follows: The phenomenon that changed with the migration to Medina led to a change in revelation and the differentiation of the jihad- invitation method in Medina. Although the phenomenon and text change the Quran has always determined how to make jihad in the way of Allah and the invitation to Islam. Jihad and invitation, which were made in the form of patience and migration in Mecca, began to be made in the form of spending and war in Medina with the change of the phenomenon. Again, in the context of invitation to Islam, the Prophet was never told to be patient in Medina, and the address of patience was directed to Muslims. In general, the jihad- invitation relationship in the Medina period can be divided into two different periods, before and after the Hudaybiya Peace. Even though Jews, hypocrites, delegations coming to Medina, and polytheist Arabs other than Quraysh were included in the call of Islam with the emigration to Medina, the Meccan polytheists have always been the main addressees of jihad and invitation. The attempt of the Quraysh to prevent the invitation to Islam, which started in Mecca, was stopped with three great jihads/wars in the Medina period, with the Treaty of Hudaybiyah, the way for the invitation to Islam was opened, and with the Conquest of Mecca, the biggest obstacle to Islam was completely removed. The enmity of the Jews of Medina, who lost their former status in Medina with the Hijra, to the call of Islam, led Muslims to jihad against them as well. In the Medina period, the obstacles to the invitation of Islam were tried to be removed through marriages as well as wars and expeditions. The Peace of Hudaybiyyah, which the revelation called a clear conquest, was an important turning point in the invitation of Islam. The Hudaybiyah Peace paved the way for the safe and secure transmission of Islam and for sending invitation letters to great giants such as Byzantium and Sassanid, and especially the polytheist Arabs in the Hijaz, who were afraid of the Quraysh, accelerated the conversion to Islam. War has never been the main target for neither the Quran nor the Prophet in the way of invitation to Islam. The main goal has always been to win people's hearts to Islam. For this reason, the Quran has recommended that if the greatest enemy, the Quraysh, approach peace, Muslims should also approach peace. Likewise, the Prophet emphasized that the conversion of a single person to Islam at the hands of a believer is better than the most valuable booty he will receive. As a result, the invitation to Islam and jihad, which started with the first revelations in Mecca, "O Prophet, get up and warn the people", and continued in line with the determination of the revelation until the Prophet's address "O Allah, did I convey the message" in the Farewell Pilgrimage at the end of the Medina period.
The Relationship of Jih?d and Dawah Medinan Period According to the Qur??n
Keywords: Tafsir; Tefsir